ANALISIS BEBAN KERJA PEGAWAI PADA BAGIAN PEMERINTAHAN KANTOR CAMAT TAMPAN KOTA PEKANBARU - Rochima Dilla; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Human resources is an important factor in the implementation of work. Good job performance is also the goal of every organization in the government and in the private sector. Human resources are the determining factor in an organization. Said to be a determining factor because the back and forth of an organization depends on its human resources. On the basis of this, it can be said the existence of human resources in an organization is an important factor. to overcome the workload problem that occurs of government kantor camat tampan town of Pekanbaru. the problem of this research is how the workload employee on the part of government kantor camat tampan town of Pekanbaru. the purpose of this study is to analyze  the workload employee on the part of government kantor camat tampan town of Pekanbaru and to analyze inhibiting factors employee on the part of government kantor camat tampan town of Pekanbaru. The theoretical concept used in this study is the analysis of workload by Suci R. Mar'ih Koesomowidjojo (2017) which starts from the conditions of work, the use of work time, targets that must be achieved. In this study researchers used qualitative descriptive research techniques. In this study researchers used observation, interview and documentation techniques. The results of this study concluded that employees worked on more than 42 weekly files for one employee.   Keywords: Workload Analysis, Human Resources